Degeneracy effects on photoionization in the solar interior - Rose,SJ (Journal of Physics D: Applied Physics, 1993)
The rate of production of solar neutrinos is very sensitive to small variations in the radiative opacity of the material at the centre of the Sun. Relatively small changes to the predicted values of the solar radiative opacity are therefore of particular relevance to the solar neutrino problem. We show that the effect of partial electron degeneracy on the photoionization cross sections is to reduce the most recent values of the solar centre opacity by 2%. © 1993 IOP Publishing Ltd.